Comparison Of Perfectionism In People Who Have Cosmetic Rhinoplasty Surgery And Control Group In Yasouj City - Marziyeh Niknam; Mohammad Fararoui; ALi Kamkar; Narges Fouladi; Ali Mohamadi (Tehran University of Medical Sciences, 2012)
Background and Aim: In recent years demand for a variety of cosmetic surgery, especially rhinoplasty has been increased in our country. Some research has shown that psychological factors influence the request for cosmetic surgery. Therefore, this study was performed to examine the dimensions of perfectionism. Materials and Methods: The study was a causation - comparative study conducted in the spring and summer of 2010 in yasouj city. Fifty people undergone rhinoplasty surgery were compared with 50 subjects as controls. For the comparison of the dimensions and subscales of perfectionism, Frost multidimensional perfectionism scale was used. Data was analysed using SPSS software and dependent t test. Results: Women using rhinoplasty were more than men. Most participants were single and between 26-30 years. The majority of the subjects had university education and their income level was between 7010000 to 9000000rials. There was significant difference in the Perfectionism subscale between the two groups in the Individual standards (P=0/001), order (P=0/001), concern about mistakes (P=0/001), parental criticism (P=0/001), doubt about action (P=0/013) and parental expectations (P=0/04). Generally the study showed significant difference in Perfectionism between the two groups(P=0/001). Conclusion: People who had cosmetic rhinoplasty surgery were more perfectionists and were often negative perfectionists.